Phylogenetic Position of Eurihaline Rotifer Brachionus sp. Originated From Tumpaan Waters, South Minahasa, North Sulawesi - Herlina Pasaribu; Inneke Rumengan; Stenly Wullur; Henki Manoppo; Joice Rimper; Reiny Tumbol (JURNAL BIOS LOGOS, 2023)
This study aims to determine the phylogenetic position of rotifer Brachionus sp. sample originated from Tumpaan coastal water, North Sulawesi in the phylogenetic tree of Brachionus spp. from 27 samples of rotifer selected from 100 samples available in NCBI Genbank. The phylogeny tree was constructed on the basis of COI (Cytochrome Oxidase I) gene sequences using MEGA7 software and the neighbor-joining method. Results show that the phylogeny tree was divided into 2 clades, the group (closely related group) and out-group (distantly related group). It is confirmed that the position of the rotifer originating from Tumpaan Coastal Water is within in group, which has closely related to the B. plicatilis complex BUS06 indicated by a bootstrap value of 80%. The group belongs to SS-type rotifers with an average body size of 149±1.3 μm. This rotifer group has been known as live prey for fish larvae with a mouth-opening size of 150 μm.